Giant quantum anharmonic effects on the stability, vibrational and optical properties of cyclo[4n+2]carbon. (October 2022) - Romanin, Davide; Calandra, Matteo
Abstract: Cyclo[ 4 n + 2 ]carbons are sp-bonded carbon rings in which Hückel rule predicts a fully symmetric structure that is, however, in competition with the second order Jahn–Teller (Peierls) distortion. This picture, however, neglects the crucial role played by nuclear quantum effects. Here we investigate the magnitude of nuclear quantum effects on the stability, vibrational and optical properties of cyclo[ 4 n + 2 ]carbons ( n = 1, 2, 3, 4 ) in vacuum. The quantum structural minimization reduces the energy separation between the different isomers and determines that the most stable C 14 isomer is the cumulenic one, setting the transition from the polyyenic to the cumulenic form at n = 3 (at odd with the classical structural optimization setting the transition at n = 2 ). Moreover, the quantum anharmonic effects generate very large frequency shifts, linewidth broadenings and satellites in the phonon spectral weight hindering any possible interpretation based on the non-interacting harmonic spectrum. The optical absorbance is completely reshaped by quantum anharmonic vibrations with redshifts ranging from 0.4 to 1.0 eV in the first excitonic absorption with respect to the static ionic picture. Finally, we also determine the crystal structure of C 18 on a NaCl bilayer to be a buckled polyynic phase in agreement with recent experimental findings. Our work outlines the crucial role of nuclear quantum effects in the understanding of carbon molecular systems.